Novel organ perfusion and preservation strategies in transplantation - where are we going in the United Kingdom? - O'Neill, S; Srinivasa, S; Callaghan, CJ; Watson, CJE; Dark, JH; Fisher, AJ; Wilson, CH; Friend, PJ; Johnson, R; Forsythe, JL; Ploeg, RJ; Mirza, DF; et al. (Lippincott, Williams and Wilkins, 2020)
This review article focuses on current clinical outcomes with novel perfusion strategies in organ transplantation. Broadly, these approaches can be divided into in situ regional perfusion in the donor and ex situ machine perfusion of individual organs. In both settings, hypothermic and normothermic techniques are in clinical use. Evidence from full text articles, abstracts, and data presented at scientific meetings has been considered. Animal studies have been excluded. The review focuses on kidney, liver, pancreas, heart, and lungs. The level of evidence ranges from quasi-experimental work in human pancreas to multiple meta-analyses of Randomized Controlled Trials for hypothermic machine perfusion of kidneys. The data in this review were presented to experts in organ perfusion and preservation at the National Health Service Blood and Transplant Preservation and Perfusion Future Strategy Summit in London in October 2018. The outcomes of the meeting are discussed in the review after due consideration of the available evidence base.